Prevalence and associated factors of self-medication among pregnant women in Sodo Town, Southern Ethiopia - Abebe, Mesfin; Gashaw, Silenat; Getahun, Dinkalem; Wassu, Wudit; Menshaw, Tiruye; Lakew, Serawit (Frontiers in Medicine, 2024)
Background Self-medication is a widespread practice among pregnant women worldwide, with 44.55% practicing it. However, it may lead to incorrect diagnosis, inappropriate treatment, and failure to recognize contraindications. The adverse effects of self-medication are often unknown, and they pose potential risks to maternal and fetal health. This study aimed to address the gap in research on the prevalence and associated factors of self-medication among pregnant women in Southern Ethiopia, and to promote effective strategies and interventions. Methods A community-based cross-sectional study was conducted among 425 pregnant women in Sodo Town from April to June 2021. Participants were enrolled using a two-stage sampling technique. Data were collected using a structured questionnaire and face-to-face interviews. The association between the outcome and independent variables was assessed through bivariate logistic regression analysis. Additionally, multivariable logistic regression analysis was carried out, including variables with an adjusted odds ratio (AOR) accompanied by a 95% confidence interval (CI) and a p-value of less than 0.05, which was considered statistically significant. Results In this study, pregnant women aged 18–39 years participated with a 100% response rate. The study found that the prevalence of self-medication during pregnancy was 20.5%, with 8.2% using herbal medicine and 12.3% using conventional medicine. A history of self-medication and first-and second-trimester pregnancy were significantly associated with self-medication. A history of self-medication (AOR = 6.31, 95% CI: 4.89, 9.91) and being in the first trimester of pregnancy (AOR = 3.47, 95% CI: 1.63, 7.38) or second trimester of pregnancy (AOR = 2.14, 95% CI: 1.12, 4.08) were associated with a higher likelihood of self-medication. Conclusion The study found that 20.5% of pregnant women engaged in self-medication. It also identified that a previous history of self-medication and gestational age were factors associated with self-medication. These findings underscore the need for targeted educational programs and policy interventions to mitigate the risks associated with self-medication during pregnancy, particularly in the early stages of gestation.